2004
DOI: 10.1016/j.concog.2004.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenal characteristics associated with projecting oneself back into the past and forward into the future: Influence of valence and temporal distance

Abstract: As humans, we frequently engage in mental time travel, reliving past experiences and imagining possible future events. This study examined whether similar factors affect the subjective experience associated with remembering the past and imagining the future.Participants mentally "re-experienced" or "pre-experienced" positive and negative events that differed in their temporal distance from the present (close versus distant), and then rated the phenomenal characteristics (i.e., sensorial, contextual, and emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

88
650
12
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 665 publications
(778 citation statements)
references
References 37 publications
(67 reference statements)
88
650
12
9
Order By: Relevance
“…Interestingly, the lower specificity was particularly marked for positive events, even after controlling for depression. It has been observed that healthy individuals imagine positive events as more specific and with a greater feeling of pre-experiencing them than negative events (D'Argembeau and Van der Linden, 2004). This positive bias has been interpreted as a way to create and maintain a positive self-concept.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the lower specificity was particularly marked for positive events, even after controlling for depression. It has been observed that healthy individuals imagine positive events as more specific and with a greater feeling of pre-experiencing them than negative events (D'Argembeau and Van der Linden, 2004). This positive bias has been interpreted as a way to create and maintain a positive self-concept.…”
Section: Discussionmentioning
confidence: 99%
“…In most of these studies, autonoetic consciousness is assessed by asking participants to rate their feeling of experiencing imagined events and feeling of travelling forward in time. 2 D'Argembeau and Van der Linden (2004) manipulated the emotional valence and temporal distance of imagined events. It was found that participants reported greater autonoetic feelings and more vivid mental representations when imagining positive rather than negative, and temporally close rather than distant, future events (see also Berntsen & Bohn, 2010;Rasmussen & Berntsen, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This is an important observation with quite broad implications. The studies of prospective thought by Newby-Clark and Ross (2003) and D"Argembeau and Van der Linden (2004) explicitly requested specific, episodic events, whereas participants in the present studies freely recalled whatever came to mind, and what came to mind tended to be general. As Conway (1992) has suggested, this level of representation is the most cognitively efficient and provides easiest access to the autobiographical memory knowledge base, and events at this level are brought to mind more easily during memory retrieval (Conway & Bekerian, 1987).…”
Section: Chapter Discussionmentioning
confidence: 75%
“…Thinking forwards and backwards in time engages similar cognitive processes and may even recruit similar neural substrates (Atance & O"Neill, 2001;Buckner & Carroll, 2007;Cabeza & St Jacques, 2007;Okuda et al, 2003;Schacter & Addis, 2007;Wheeler et al, 1997). D"Argembeau and Van der Linden (2004) found many perceptual and affective attributes were shared by specific past and future events elicited by wordcues. The phenomenology and specificity of both types of event were also mediated by temporal distance, such that temporally near past and future events evoked a stronger sense of being "re(pre)-experienced" and contained more sensorial and contextual detail than did temporally distant events.…”
Section: Thinking About Past and Future Autobiographical Experiencementioning
confidence: 99%
See 1 more Smart Citation